Thermal and mechanical properties of CeO2. Issue 4 (20th September 2018) - Suzuki, Kiichi; Kato, Masato; Sunaoshi, Takeo; Uno, Hiroki; Carvajal‐Nunez, Ursula; Nelson, Andrew T.; McClellan, Kenneth J.
Abstract: The thermal and mechanical properties of cerium dioxide (CeO2 ) were assessed using a range of experimental techniques. The oxygen potential of CeO2 was measured by the thermogravimetric technique, and a numerical fit for the oxygen potential of CeO2 is derived based on defect chemistry. Mechanical properties of CeO2 were obtained using sound velocity measurement, resonant ultrasound spectroscopy and nanoindentation. The obtained mechanical properties of CeO2 are then used to evaluate the Debye temperature and Grüneisen constant. The heat capacity and thermal conductivity of CeO2 were also calculated using the Debye temperature and the Grüneisen constant. Finally, the thermal conductivity was calculated based upon laser flash analysis measurements performed on pellets fabricated using a range of feedstock purities to resolve discrepancies in the existing literature.